Clinicopathological analysis of pleomorphic carcinoma of the lung: Diffuse ZEB1 expression predicts poor survival. Issue 1 (January 2015) - Miyahara, So; Hamasaki, Makoto; Hamatake, Daisuke; Yamashita, Shin-ichi; Shiraishi, Takeshi; Iwasaki, Akinori; Nabeshima, Kazuki
Highlights We examined ZEB1 expression and clinicopathology in 62 pleomorphic carcinoma (PC). Diffuse ZEB1 expression in PC was significantly associated with shorter survival. Diffuse ZEB1 expression was an independent poor prognostic factor in PC.